Cervical Cancer, Papillomavirus, and miRNA Dysfunction - Bañuelos-Villegas, Evelyn Gabriela; Pérez-yPérez, María Fernanda; Alvarez-Salas, Luis Marat (Frontiers in Molecular Biosciences, 2021)
Cervical cancer is the leading cause of death by cancer in women from developing countries. Persistent infection with high-risk human papillomavirus (HPV) types 16 and 18 is a major risk factor for cervical carcinogenesis. Nevertheless, only a few women with morphologic expression of HPV infection progress into invasive disease suggesting the involvement of other factors in cervical carcinogenesis. MicroRNAs (miRNAs) are conserved small non-coding RNAs that negatively regulate gene expression including genes involved in fundamental biological processes and human cancer. Dysregulation of miRNAs has been widely reported in cervical cancer. This work focuses on reviewing the miRNAs affected during the HPV infection process, as well relevant miRNAs that contribute to the development and maintenance of malignant cervical tumor cells. Finally, we recapitulate on miRNAs that may be used to distinguish between healthy individuals from patients with precancerous lesions or cervical tumors.